Smart objects and technologies for social good : third International Conference, GOODTECHS 2017, Pisa, Italy, November 29-30, 2017, Proceedings /: third International Conference, GOODTECHS 2017, Pisa, Italy, November 29-30, 2017, Proceedings. (2018) - Unknown
No abstract available